RELABELING BY INFLUENCERS IN THE DIGITAL MARKETPLACE: A Legal Analysis Under Indonesian Law, Islamic Commercial Ethics, and FTC Regulations - Robbani, Shofa; Fitriani, Dinda Oktavia Bulan; Alias, Muhammad Nazir; Laili, Dwi Nur; Maulana, M. Iqbal; Afida, Yuni Salma Nur; Sholihah, Amaliatus (Institut Agama Islam Negeri Metro, 2025)
This research is a normative legal study using a case study approach that analyzes the legal and ethical implications of relabeling practices conducted by influencers in Indonesia. The problem arises from the case of Shella Saukia and Umama Scarf, in which original hijab products were resold after their brand labels were replaced with a private “SS” label without authorization. This practice poses serious legal concerns regarding consumer deception, violation of trademark rights, and unfair business competition in digital commerce. The study relies entirely on secondary data through library research, using primary legal materials such as Law Number 8 of 1999 on Consumer Protection, Law Number 20 of 2016 on Trademarks and Geographical Indications, and Regulation of the Minister of Trade Number 73 of 2015 on Mandatory Labeling on Goods. The analysis applies a normative qualitative method by correlating Indonesian positive law with principles of fiqh muamalah—particularly ṣidq (honesty), bayān (transparency), and ‘adālah (justice). The findings show that unauthorized relabeling violates consumers’ rights to accurate information, infringes trademark protection, and distorts fair market competition. From an Islamic legal perspective, such practices constitute tadlīs (deception), gharar (uncertainty), and ghasb (unlawful appropriation), all of which are categorically prohibited. As a comparative framework, this study also refers to the United States Federal Trade Commission (FTC) regulations, which strictly mandate truth-in-labeling and prohibit deceptive or unfair marketing practices. These standards provide valuable insight for strengthening Indonesia’s regulatory safeguards. The study concludes that harmonizing positive law, Islamic legal principles, and international best practices is essential to ensuring a fair, transparent, and ethical digital trade ecosystem.